2005
DOI: 10.1002/crat.200410444
|View full text |Cite
|
Sign up to set email alerts
|

Growth and optical characterization of cerium and lead‐doped Bi12TiO20 sillenite single crystals

Abstract: Bi 12 TiO 20 (BTO) single crystals doped with PbO and CeO 2 were grown by the Top Seeded Solution Growth (TSSG) technique from the liquid phase with nominal compositions of 10Bi 2 O 3 : (1-x)TiO 2 : x PbO and 10Bi 2 O 3 : (1-x)TiO 2 : xCeO 2 with x = 0.25 and 0.10. No growth-related difficulties were encountered other than those typical of sillenite crystals. Samples with good optical quality were obtained and were characterized by optical absorption, dark current, spectral photocurrent dependence, optical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…A study of partial replacement of the Te ions in the Bi6Te2-xRxO13 (R = Ti, Si and Ce) composition was done in order to minimize or avoid the oxidation of Te 4+ to Te 6+ during the cubic/orthohrombic phase transition. The addition of intentional impurities in crystalline compounds is an important tool in the materials chemistry and the object of numerous studies [13][14][15][16][17][18][19][20][21][22][23][24], in particular, there was an investigation of the stabilization of this cubic phase (Bi6Te2O13) at room temperature by replacing Bi ions [24]. Here, Ti, Si and Ce ions have been chosen to replace Te ion site because all of these ions present the same oxidation state (IV) and ionic radius close.…”
Section: Introductionmentioning
confidence: 99%
“…A study of partial replacement of the Te ions in the Bi6Te2-xRxO13 (R = Ti, Si and Ce) composition was done in order to minimize or avoid the oxidation of Te 4+ to Te 6+ during the cubic/orthohrombic phase transition. The addition of intentional impurities in crystalline compounds is an important tool in the materials chemistry and the object of numerous studies [13][14][15][16][17][18][19][20][21][22][23][24], in particular, there was an investigation of the stabilization of this cubic phase (Bi6Te2O13) at room temperature by replacing Bi ions [24]. Here, Ti, Si and Ce ions have been chosen to replace Te ion site because all of these ions present the same oxidation state (IV) and ionic radius close.…”
Section: Introductionmentioning
confidence: 99%
“…In sillenite family, Bi12TiO20 (BTO) crystals present some practical advantages for photorefractive applications, such as lower optical activity, higher electro-optic coefficient, higher photoconductivity and increased sensitivity to red light [1], and the influence of impurities on the properties affecting the photorefractive response of BTO has been subject of extensive research [3][4][5][6][7]. However, the search for new compositions resulting in crystals with improved photorefractive response remains as a present challenge.…”
Section: Introductionmentioning
confidence: 99%
“…15 Cerium doping of bismuth titanium oxide (Bi 12 TiO 20 , BTO) increased the dark current and photosensitivity for l of 600 to 450 nm, although the optical activity, electrooptic coefficient and optical absorption remained unchanged in BTO:Ce. 16 The XRD showed that 5% of Ce doping into the perovskite B-site can make the BaFeO 3Àd transform from the hexagonal structure to the cubic structure. 17 The piezoelectric constant dependence on Ce content for Pb 1Àx Ce x (Zr 0.52 Ti 0.48 )O 3 ceramics has been reported.…”
Section: Introductionmentioning
confidence: 99%